The Influence of Using the Student Facilitator and Explaining Model in Learning Speaking Skills at Madrasah Ibtidaiyah - Arini Purnamasari; Farida Nugrahani; Suwarto Suwarto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to determine whether there is an influence of the Student Facilitator and Explaining (SFAE) model on students' speaking skills at Madrasah Ibtidaiyah. This research method uses Quasi Experimental Design, a form of Nonequivalent Control Group Design. The data for this research are the results of learning speaking skills using the Student Facilitator and Explaining (SFAE) model. The sample for this research was 40 Madrasah Ibtidaiyah students. Data collection techniques include interviews and questionnaires. Before analysis, the data was tested using expert validity, normality and homogeneity tests. Next, a hypothesis test was carried out using T test analysis (T-Test), namely the Independent Simple T-Test. Output results of the normality test using the Shapiro Wilk test with the help of SPSS version 20. 0 for windows by looking at the Pretest data, the experimental class value is 0.379 > 0.05 and the control class value is 0.491 > 0.05, indicating that the data variance for the experimental class and control class is normally distributed. After knowing that the samples are normally distributed, the next step is to carry out a normality test to find out whether the two samples have the same variance. The statistical analysis used to test homogeneity is the homogeneity of variance test (F Test) with the help of SPSS version 20.0 for Windows. Significance level >0.05. Data is declared homogeneous if the significant value is greater than 5% or 0.05. The results of the research showed that the control class got an average pretest to posttest score which increased. In the experimental class, the average student pretest to posttest scores also increased. In the analysis of hypothesis testing using the t test (independent sample t test) by comparing the experimental class posttest data with the control class posttest, it shows that the application of the Student Facilitator and Explaining (SFAE) learning model has no effect on the speaking skills of students at Madrasah Ibtidaiyah.